Tingkat Pengetahuan Dan Persepsi Masyarakat Tentang Vaksin Covid-19 Studi Kasus : Kota Gorontalo - Teti Sutriyati Tuloli; Widy Susanti Abdulkadir; Nurain Abdullah; Mohamad Aprianto Paneo (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
Covid-19 is a source of problem in the world because of the continuous increse. Due to the number of cases exposed, thus it is necessary to take preventive measures to break the spread of the Covid-19 virus. Covid-19 for Covid-19 is an effort to protect oneself against or to attack the disease and increase the immune system. In general, the sommunities cannot receive vaccinations becaus they are concerned about the safety and effectiveness of vaccines. However, understanding and accepting the Covid-19 vaccine in Indonesia continues to increase. This research aims to detemine the level of public knowledge and perception and the relationship between knowledge and perception of the Covid-19 vaccine in the Limba U II Village, Kota Selatan Subdistric, Gorontalo City. This research employs observational research with a descriptive quantitative design and a cross-sectional approach. In this research, 372 samples are obtained from the questionnaire distribution. Data are analyzed using Chi-Square. The results indicate that the level of public knowledge in Limba U II Village about the Covid-19 vaccine is the high category (60%), and the public perception in Limba U II Village is in a postivie category (62,1%). The relationship between the two shows significant results with P-Value = 0,000, where the value is less than 0,05.